Teenagers’ Challenges and its Implications on Social Adjustment of Secondary School Students in Obio/Akpor Local Government Area of Rivers State - Daminabo, D. A. F; Teibowei J.; Ajibua, O. M (International Journal on Economics, Finance and Sustainable Development, 2022)
The study investigated teenagers’ challenges and its implications on social adjustment of secondary school students in the study area. The study was a comparative study that adopted the correlational research design. The forty (40) items instrument or questionnaire, were constructed and structured for the study. The respondents (i.e. students involved in street trading) were among those selected secondary school students in Obio-Apkor and Port-Harcourt Local Government Areas of Rivers state, simple sampling techniques was used to drew all the respondents and two hundred (200) as the sample size for the study from a Population of two thousand five-hundred, (2,500). Mean, criterion mean, and standard deviation were used for answering the research questions. The study revealed that engaging in petty business led to student mixing business with schooling when they are supposed to be in the class; this affected their performance, study habit and made them to absent themselves from classes. Furthermore, the lack of concentration even when they attend school sparingly also affected their concentration and performance in secondary schools. It was recommended that; the Government should set up laws that would bar school age children from engaging in street trading or buying of alcohol. Social workers should become part of the school administrative staff for monitoring illegal activities among secondary schools students in the study area.